Pemanfaatan Peta Administrasi dalam Penyajian Informasi Wilayah dan Potensi Wisata Desa Busung - Riska Putri Sari (Yayasan Daarul Huda Kruengmane, 2026)
Maps are strategic instruments in presenting spatial information, functioning not only as visualization media but also as analytical tools to understand regional conditions, identify potentials, and formulate directions for sustainable development. In Busung Village, Seri Kuala Lobam District, Bintan Regency, local potentials remain poorly documented and difficult to access, resulting in suboptimal utilization in both development planning and tourism promotion. This condition poses a challenge for local authorities and communities to provide spatial information that is accurate, attractive, and easily understood. To address this issue, a Community Service Program (Kuliah Kerja Nyata/KKN) was carried out through QGIS-based mapping using a descriptive and participatory approach involving local communities and village officials. Data were collected through field observation, interviews, documentation, and satellite imagery processing using QGIS software. The mapping results not only display the administrative boundaries but also visualize the distribution of public facilities, natural attractions, cultural heritage sites, and conservation areas such as mangrove plantations. This activity expands access to spatial information for the community and stakeholders to better understand the geographical characteristics of Busung Village. Through this program, local residents gain hands-on experience in utilizing spatial technology to support decision-making, tourism promotion, and environmental conservation. Therefore, QGIS-based mapping serves not only as an educational and promotional medium but also as a strategic instrument to strengthen village identity and to promote inclusive, participatory, and sustainable development at the local level.